Evaluating the impacts of urban freight traffic: application of micro-simulation at a large establishment - Aditjandra, Paulus T.; Galatioto, Fabio; Bell, Margaret C.; Zunder, Thomas H. (European Journal of Transport and Infrastructure Research, 2016)
Heavy Goods Vehicles, HGV, and Light Goods Vehicles, LGV, are a significant contributor to air pollution problems in urban areas. This paper quantifies the contribution to the environment of the deliveries to a single, large city employer addressing a research gap in the literature. Analysis of data from comprehensive surveys carried out over two years demonstrated that freight delivery traffic generated by an urban establishment with multiple properties in a compact urban setting, is characterised by a high proportion of LGV consistent with recent national and international trends. Also, despite freight traffic is only 10% of local traffic, more than 50% serves the single establishment, suggesting a different approach to policy making driven by the employer should be explored. The modelling results showed, relatively, the largest contribution to total emissions comes from HGVs in the AM peak, 13.8%, 43.7%, 9.2% for CO2, NOx and PM respectively. LGV contribute less, with 5.5%, 3.8%, 6% for CO2, NOx and PM respectively but more responsible for local congestion due to their numbers. This research is the first known study of its type and with the unique combination of measurement and traffic microsimulation allowed consideration of more effective traffic management strategies as well as providing evidence to support a consolidation centre for deliveries outside the city with fewer electric or low emissions last mile vehicles reducing substantially the environmental impact. The research outputs are relevant to many other similar cases in UK and Europe. The paper contributes to the ongoing development of research and policy looking to achieve sustainable urban logistics through receiver and purchasing led initiatives.